Improved methods for mare milk analysis: Extraction and quantification of mare milk carbohydrates and assessment of FTIR-based macronutrient quantification - Pyles, Morgan B.; Brock, Kristin; Schendel, Rachel R.; Lawrence, Laurie M. (Frontiers in Nutrition, 2023)
Accurately determining the macronutrient profile of mare milk is a precursor to studying how milk composition affects foals’ growth and development. This study optimized and validated an extraction and quantification method for mare milk oligosaccharides, which make up a portion of the carbohydrate fraction of mare milk. Mare milk was extracted with chloroform and methanol, and oligosaccharides were selectively isolated from the carbohydrate fraction using porous-graphitized carbon solid-phase-extraction (SPE). Good recovery rates for milk oligosaccharides (between 70 and 100%) were achieved with the optimized method. This study also compared the use of Fourier-Transform infrared (FTIR) spectroscopy versus wet chemistry quantification methods for protein, fat, and lactose. The FTIR method produced statistically equivalent protein contents to the wet chemistry method, along with substantial savings in both analyst time and consumable consumption. FTIR analysis slightly underestimated the fat content of mare milk relative to the official wet chemistry method, with the difference between the methods increasing at higher fat contents. FTIR also overestimated the lactose content of mare milk and appeared to generate “lactose” values that included the milk oligosaccharides and thus represented the total carbohydrate (lactose and milk oligosaccharides) content of mare milk.